ANALISIS PENDAPATAN DAN DAYA SAING USAHA TERNAK SAPI POTONG DI KABUPATEN MUNA - Safri Lasahudu; Ayub M. Padangaran; La Ode Nafiu (Jurnal Sosio Agribisnis, 2017)
The study was conducted in Tongkuno District aimed at knowing livestock business income, and analyzing the competitiveness of beef cattle business. Data came from 78 respondents interviewed using a questionnaire. The variables observed included aspects of production: seeds / feeders, feed, cages, labor, agricultural feed, equipment and medicines; and aspects of income were livestock sales. Data were analyzed using income analysis and Polycy Analysis Matrix (PAM) to analyze competitiveness. The results showed that farmers' income was Rp. 2,319,102,935 with an average income per year is Rp. 5,946,418, and this activity is feasible to be developed with an R/C ratio = 1.6. The analysis shows that the competitiveness of beef cattle farms in competentive Tongkuno District competes with a PCR value of 0.6 and has comparative competitiveness with a DRC value of 0.8.Keywords: income analysis, beef cattle, competetive, comparative